Incorporating human dimensions objectives into waterfowl habitat planning and delivery - Patrick K. Devers; Anthony J. Roberts; Scott Knoche; Paul I. Padding; Robert Raftovich (Wildlife Society Bulletin)
ABSTRACT The 2012 revision of the North American Waterfowl Management Plan (NAWMP) explicitly recognized the need to increase recruitment and retention of waterfowl hunters, birdwatchers, and other conservationists to maintain support for wetland conservation. The incorporation of human dimensions objectives within the NAWMP has compelled waterfowl and wetland managers to consider whether and to what extent landscape characteristics such as public land access; the type, amount, and location of wetlands; and site infrastructure will increase support for wetland conservation among user groups. Further, it has forced the waterfowl community to consider the possible trade‐offs between managing land to achieve biological versus social objectives. We used publicly available, long‐term data sets to illustrate a method of incorporating human dimensions into waterfowl habitat planning and management. We used United States Fish and Wildlife Service waterfowl harvest survey data, United States Geological Survey band encounter data, and Cornell Lab of Ornithology eBird data to summarize travel characteristics of wetland bird enthusiasts (i.e., waterfowl hunters and birdwatchers) in the Atlantic Flyway. Greater than 90% of all trips by wetland bird enthusiasts occurred within their state of residence. We used data from New York, USA, to demonstrate how to construct discrete choice recreation demand models to identify factors that influence site selection and participation. We demonstrate how model outputs, such as the expected change in the number and geographic distribution of recreational trips (i.e., hunting or birdwatching), can be used as an objective metric to evaluate the benefits of alternative habitat acquisition and restoration projects relative to the human dimensions objective of the NAWMP. These data and methods show promise for incorporating human dimensions objectives into habitat delivery and understanding potential trade‐offs relative to biological objectives. Published 2017. This article is a U.S. Government work and is in the public domain in the USA.